Relationen mellan lärares intentioner och deras respons till elever: En studie om återkoppling som stöd för matematisk resonemangsförmåga på mellanstadiet - Balan, Andreia; Jönsson, Anders (Educare, 2021)
Formative feedback has the potential to support student learning and performance. However, teachers sometimes have difficulties realizing their intentions with formative feedback when responding to students’ questions or solutions. If the actual response provided does not agree with the teacher’s intentions, the formative potential may be diminished or lost. The purpose of this study is therefore to investigate whether teachers themselves are able to identify the correspondence between their stated intentions and their actual response to students. Four teachers participated in the study by responding to the mathematical reasoning performed by twelve students in grades 4-5 (the feedback situations were recorded) and then taking part in stimulated-recall interviews. The results show that the teachers were able to identify certain instances of correspondence, and/or differences, between their intentions and how they acted in the feedback situations. The differences identified by the teachers were justified based on the teachers’ individual beliefs – for instance, the belief that some mathematical methods belong to certain grade levels and should not be taught in advance – or on concerns about how the students would react.